2010
DOI: 10.1111/j.1365-277x.2010.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Important psychosocial factors to target in nutrition interventions to improve diet in Inuvialuit communities in the Canadian Arctic

Abstract: Background:  With increasing chronic disease amongst Inuvialuit in the Canadian Arctic, research on dietary behaviours and their determinants in this population is needed to develop nutritional behaviour change intervention strategies. The present study aimed to assess the knowledge, self‐efficacy and intentions towards healthy eating and healthy eating behaviours of Inuvialuit adults in the Northwest Territories (NWT), Canada. Methods:  The Adult Impact Questionnaire was developed from behavioural theories an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…In this study, factors affecting low-income AA HMP in Baltimore, including beliefs, attitudes, and psychosocial factors toward healthy eating, are comparable to those affecting other demographic groups (Fulkerson et al 2010; Kornides et al 2014; Kramer et al 2012; Mead et al 2010). For example, positive perceptions concerning healthy food were positively and significantly associated with higher frequencies of HMP among children and adolescents in Canada (Woodruff and Kirby 2013), African American youth in Baltimore (Kramer et al 2012), adolescents and parents of various socioeconomic statuses in Minnesota (Fulkerson et al 2010), and Inuvialuit adults in Canada (Mead et al 2010).…”
Section: Discussionmentioning
confidence: 76%
“…In this study, factors affecting low-income AA HMP in Baltimore, including beliefs, attitudes, and psychosocial factors toward healthy eating, are comparable to those affecting other demographic groups (Fulkerson et al 2010; Kornides et al 2014; Kramer et al 2012; Mead et al 2010). For example, positive perceptions concerning healthy food were positively and significantly associated with higher frequencies of HMP among children and adolescents in Canada (Woodruff and Kirby 2013), African American youth in Baltimore (Kramer et al 2012), adolescents and parents of various socioeconomic statuses in Minnesota (Fulkerson et al 2010), and Inuvialuit adults in Canada (Mead et al 2010).…”
Section: Discussionmentioning
confidence: 76%
“…The Inuvialuit component of HFN included three of the six ISR communities, where two received the intervention and one served as a control group with delayed intervention. Program impacts were evaluated in relation to psychosocial (Mead, Gittelsohn, De Roose, & Sharma, 2010a;Mead, Gittelsohn, Roache, Corriveau, & Sharma, 2013) socio-economic , healthy eating behaviour, and diet quality outcomes (Bains et al, 2014;Kolahdooz, Butler, et al, 2014;Zotor et al, 2012). Overall, HFN showed some success in mitigating the negative impacts of the nutrition transition among Inuvialuit.…”
Section: Nutrition Education and Food Preparation Programsmentioning
confidence: 99%
“…There was a significant increase in the use of healthy preparation methods within 12 months. The pre-intervention evaluation of this population indicated that pan-frying with fat was one of the most frequently reported methods of preparation [18,19]. Post-intervention results from the intervention communities indicated a decrease in the use of this method and a concurrent increase in the use of pan-frying methods that did not add fat, thereby reducing added fat consumption in the population under intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies found a high prevalence of preparation methods that add fat to foods (e.g. frying with lard) [18,19]; these preparation methods are determinants of fat intake [20,21] and risk factors for impaired glucose tolerance [22] among Inuit and Inuvialuit populations.…”
Section: Introductionmentioning
confidence: 99%